Islam in China seas: Islam and Muslims in Myanmar - U Tun Aung, Maulana Akbar Shah (IIUM Press, International Islamic University Malaysia, 2018)
In China seas, Malakka strait has been a center of trade zone for Asian countries today. It has been a strategic maritime root where kingdoms of Majapahit, Tiriwizara, Malakka Kingdom, Pagan, Hantawaddy and Konbong Kingdoms of Myanmar benefited tremendously. Trade and diplomatic relationship Between China and Burma has been traditionally excellent till date for they are connected by land as well as sea. Burma, presently called Myanmar has been an important country from the perspective of geo-politics in the region, but the history of Muslims with the population of 5 million in this country beyond the Second World War II has been worse to the extent, they are struggling for survival. Muslims have been living in Myanmar for the last few thousand years. The previous Buddhist rulers of the country and the British administration that followed, provided full rights of citizenship to them without discrimination. Thus, they enjoyed every segment of life, business, the community, society, educational institutions and politics. In the light of these welcoming circumstances, Muslims were happy to contribute to the nation by joining the army, the police force, government institutions such as health care, education, trade, business, agriculture as well as in politics and as legislators in the parliament of Myanmar. Nevertheless, their unfortunate history began when military rule came into power in 1962. All the rights and responsibilities they had enjoyed over the years became restricted. Discrimination policies were applied in every segment of national institutions even their citizenship rights were threatened. The discrimination continued to the extent that their racial status as one of the 145 races of Myanmar was removed. Consequently, frequent riots, afflictions and violence against Muslim minorities became the norm, resulting in a peaceful coexistence between Muslim minorities and the majority Buddhists becoming impossible. The objective of this paper was to research the historical existence and identification of Muslims in Myanmar. It is hoped that the findings of this work will support a theory of peaceful coexistence between Muslims and Buddhists in Myanmar.